Historia de las Indias (1552) - López de Gómara, Francisco (Sources de la Casa de Velázquez, 2021)
F. López de Gómara's Historia de las Indias is the only chronicle of the Indies in the sixteenth century to offer a complete overview of the process of discovery and conquest, even though the author had never been to the Indies. The intelligence and elegance of Gómara's style explain the remarkable success of the work both in Spain and in Europe, in spite of a diffusion disrupted by the prohibition decrees from 1553. Of the two parts that compose it, it is the first, critically edited here, that has had the greatest influence on the history of ideas.